IMPLEMENTASI PROGRAM PENINGKATAN KOMPETENSI PROFESIONAL GURU DI TAMAN KANAK- KANAK NEGERI 1 SUMBAWA BESAR - M Maudara; Muhammad Ikhsan (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
This study aims to describe the implementation of teacher professional competency development at TK Negeri 1 Sumbawa Besar, explain the results and impacts, and identify obstacles and supporting factors in its implementation. This study used a qualitative method with a phenomenological approach and a case study design. Data were collected through in-depth interviews, participant observation, and documentation studies. Informants were selected intentionally using a purposive sampling technique. Data trustworthiness was ensured through credibility, dependability, and confirmability checks, while data analysis was conducted using interactive analysis techniques proposed by Miles and Huberman. The findings indicate that teacher professional competency development is carried out through face-to-face education and training programs, workshops on the preparation and development of the Independent Curriculum for Early Childhood Education, technical guidance on the development of learning media, in-house training on in-depth learning in the context of implementing the Independent Curriculum, and independent training through digital platforms such as webinars. The implementation of these activities has a positive impact on improving teacher quality in the learning process, creating a more engaging and enjoyable learning environment, increasing student learning motivation, and improving teacher skills in implementing early childhood learning, designing learning assessments, managing interactive learning, understanding the curriculum, developing extracurricular activities, and integrating digitalization into learning. Barriers and supporting factors in improving teacher professional competence come from internal and external factors, including motivation, integrity, professional commitment, mastery of information technology, and teacher growth mindset.